2014
DOI: 10.1016/j.nuclphysa.2014.08.092
|View full text |Cite
|
Sign up to set email alerts
|

Collective effects in light–heavy ion collisions

Abstract: We present results for the azimuthal anisotropy of charged hadron distributions in A+A, p+A, d+A, and 3 He+A collisions within the IP-Glasma+music model. Obtained anisotropies are due to the fluid dynamic response of the system to the fluctuating initial geometry of the interaction region. While the elliptic and triangular anisotropies in peripheral Pb+Pb collisions at √ s = 2.76 TeV are well described by the model, the same quantities in √ s = 5.02 TeV p+Pb collisions underestimate the experimental data. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Recently it has been observed that flow-like multi-particle correlations also exist in small systems, such as the ones created in high energy p+p, d+Au and p+Pb collisions. While it is still being debated if the origin of these correlations is hydrodynamic evolution as it is in nucleus-nucleus collisions [280][281][282], it is interesting to see if these flow-like correlations disappear at lower collision energies. Such a measurement has been recently carried out by the PHENIX collaboration [283] and in Fig.…”
Section: Flow In Small Systemsmentioning
confidence: 99%
“…Recently it has been observed that flow-like multi-particle correlations also exist in small systems, such as the ones created in high energy p+p, d+Au and p+Pb collisions. While it is still being debated if the origin of these correlations is hydrodynamic evolution as it is in nucleus-nucleus collisions [280][281][282], it is interesting to see if these flow-like correlations disappear at lower collision energies. Such a measurement has been recently carried out by the PHENIX collaboration [283] and in Fig.…”
Section: Flow In Small Systemsmentioning
confidence: 99%
“…A sizeable v 3 is found, which can be connected to the initial triangular asymmetries. The curves in the figure show several model calculations that include a fluid-expansion stage in to model the collision and produce the anisotropy in the final state [11,16,17,18,19]. The model curves are in good qualitative agreement with the measurements.…”
Section: Long-range Correlations In Small Systemsmentioning
confidence: 57%
“…The agreement is better with the SONIC model, but the uncertainties on the data do not allow yet to invalidate the existence of the pre-equilibrium flow in these systems. The model with IPGlasma initial state and then hydrodynamical evolution [6] largely underestimates the data in p+Au collisions, while overestimates the measured flow in the d+Au and 3 He+Au collisions. Figure 2 shows the measured preliminary STAR data of v even 1 , v 3 and v 2 measurements in various collision systems from very large (U + U and Au + Au ) to moderately large (Cu + Au and Cu + Cu ) to small systems (d+Au and p+Au ).…”
Section: Study Of the Initial Geometrymentioning
confidence: 77%